(untitled) (Research, Society and Development, 2021)
Cookies like widely consumed by people of all age groups, however they are usually made from refined flours. Thinking of improving the nutritional characteristics of the biscuit, the objective of this study was to develop a cookie based on mixed flour from beet stalks (FTB) and oat flakes (FA) in association with wheat flour (FT). Cookies were developed using the simplex centroid experimental design, with a central point and restriction of the maximum limit of wheat flour by 50%. In the cookies, the proximate composition and purchase intention were determined. The influence of the mixture on the variables moisture, total fiber, insoluble fiber, soluble fiber, ash, carbohydrates and purchase intention was explained by the linear model, whereas the quadratic model was more adequate to justify the effect of the flour on the content of protein in cookies. The proposed models were unable to explain the influence on the lipid content of the cookies. FTB was associated with cookies with higher moisture, fiber, ash and water activity content, with an antagonistic effect on carbohydrate content and acceptance. FAs, on the other hand, showed a synergistic effect on the protein content of cookies. Therefore, the association of FTB and FA proved to be promising to improve the nutritional quality of cookies. However, it is noteworthy that the FTB should not exceed 17% of the meal base to avoid interfering with the acceptance of the product.